Systematic Review of Functional Mapping and Cortical Reorganization in the Setting of Arteriovenous Malformations, Redefining Anatomical Eloquence - Soldozy, Sauson; Akyeampong, Daniel K.; Barquin, David L.; Norat, Pedro; Yağmurlu, Kaan; Sokolowski, Jennifer D.; Sharifi, Khadijeh A.; Tvrdik, Petr; Park, Min S.; Kalani, M. Yashar S. (Frontiers in Surgery, 2020)
Objective: The goal of this study was to systematically review functional mapping and reorganization that takes place in the setting of arteriovenous malformations (AVMs) and its potential impact on grading and surgical decision making. Methods: A systematic literature review was performed using the PubMed database for studies published between 1986 and 2019. Studies assessing brain mapping and functional reorganization in AVMs were included. Results: Of the total 84 articles identified in the original literature search, 12 studies were ultimately selected. This includes studies evaluating the impact of cortical reorganization on patient outcomes and factors impacting and triggering cortical reorganization in AVM. Conclusion: These studies demonstrate the utility of preoperative brain mapping and acknowledgment of functional reorganization in the setting of AVMs. While these findings led to alterations in Spetzler–Martin grading and subsequent surgical decision making, it remains unclear the clinical utility of this information when assessing patient outcomes. While promising, more research is required before recommendations can be made regarding functional brain mapping and cortical reorganization with respect to AVM surgery involving eloquent brain tissue.